2010
DOI: 10.1002/adsc.200900693
|View full text |Cite
|
Sign up to set email alerts
|

One Step Synthesis of Chiral Olefins via Asymmetric Diamination and their Applications as Ligands for Rhodium(I)‐Catalyzed 1,4‐Additions

Abstract: A variety of acyclic chiral dienes were synthesized in a single step via palladium(0)-catalyzed asymmetric allylic and homoallylic C À H di-A C H T U N G T R E N N U N G amination of terminal olefins. The applications of such simple dienes as steering ligands for rhodi-A C H T U N G T R E N N U N G um(I)-catalyzed asymmetric 1,4-additions afforded the corresponding adducts in excellent yields and up to 85% ee.Keywords: acyclic chiral dienes; asymmetric catalysis; asymmetric diamination; conjugated addition; di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 49 publications
0
18
0
1
Order By: Relevance
“…Notably, the enantioselectivities were also very high for arylmethylene cyanoacetates where the aryl groups were 2-methylphenyl, 2-naphthyl, and 4-chlorophenyl (Table 39). 141 A highly stereoselective synthesis has been reported by the chiral diene/rhodium-catalyzed stereoselective 1,4-addition of arylboronic acids 2 to b-aryl-substituted a,b-unsaturated aldehydes and esters 1u,v, which gave the corresponding b,b-diaryl substituted products 145a, b with 90-93% ee 142-144 (Scheme 56).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the enantioselectivities were also very high for arylmethylene cyanoacetates where the aryl groups were 2-methylphenyl, 2-naphthyl, and 4-chlorophenyl (Table 39). 141 A highly stereoselective synthesis has been reported by the chiral diene/rhodium-catalyzed stereoselective 1,4-addition of arylboronic acids 2 to b-aryl-substituted a,b-unsaturated aldehydes and esters 1u,v, which gave the corresponding b,b-diaryl substituted products 145a, b with 90-93% ee 142-144 (Scheme 56).…”
Section: Methodsmentioning
confidence: 99%
“…In 2009, Du and co-workers found that 1,5-hexadiene can act as an effective ligand for Rh I -catalyzed 1,4-addition of phenylboronic acid (25 a) to 2-cyclohexenone (24 a) to give the corresponding adduct 26 a with quantitative conversion (Scheme 4). [25] Inspired by this experimental result, the known compound (3R,4R)-hexa-1,5-diene-3,4-diol (27) was also used as a ligand for this reaction. Significantly, with the use of such a simple diene ligand bearing just two terminal olefins, the desired product 26 a was obtained in 98 % yield with 82 % ee (Scheme 4).…”
Section: Chiral-chain Dienesmentioning
confidence: 99%
“…[18] Recent studies on chiralchain diene ligands have demonstrated that two simple terminal olefin moieties can ensure satisfactory activity and selectivity. [25,27,28,[30][31][32] Therefore, the combination of terminal olefins and a phosphorus atom, which gives stronger coordination ability, on suitable chiral frameworks possibly provides a practical strategy for developing novel P/olefin hybrid ligands.…”
Section: P/terminal Olefin Hybrid Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Furthermore, chiral, non-racemic imidazolidin-2-ones have been employed as chiral auxiliaries [8,9] and as scaffolds for bis(phosphine) ligands [10,11] for use in enantioselective synthesis. A number of approaches to construction of the imidazolidin-2-one ring have been developed [1220] including carbonylation of vicinal diamines, [13] oxidative diamination of alkenes with ureas, [14,15] and electrophilic cyclization [16] or transition metal-catalyzed carboamination of N -allylic ureas. [17,18] In contrast, transition metal-catalyzed alkene hydroamination, which represents perhaps the most conceptually simple and atom-economical approach to the cyclization of readily available N -allylic ureas, has gone largely unexplored as a route to the imidazolidin-2-one ring.…”
Section: Introductionmentioning
confidence: 99%